2023
DOI: 10.1186/s13046-023-02639-8
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic circulating miRNA signature as orchestrator of cell invasion via TKS4/TKS5/EFHD2 modulation in human gliomas

Abstract: Background Altered microRNA profiles have been observed not only in tumour tissues but also in biofluids, where they circulate in a stable form thus representing interesting biomarker candidates. This study aimed to identify a microRNA signature as a non-invasive biomarker and to investigate its impact on glioma biology. Methods MicroRNAs were selected using a global expression profile in preoperative serum samples from 37 glioma patients. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“… ROC curve analysis showed that serum miR-145–5p could effectively distinguish GBM patients from the control groups. Multivariate analysis confirmed that serum miR-145–5p expression was an independent prognostic indicator for overall survival in GBM patients Díaz Méndez et al ( Diaz Mendez et al, 2023 ) 2023 miR-1-3p Underexpressed Serum Diagnosis, Prognosis A 3-microRNA signature consisting of miR-1-3p, miR-26a-1-3p, and miR-487 b-3p was found to be differentially expressed in the serum of glioma patients compared to healthy controls. This 3-microRNA signature was specifically downregulated in the serum of glioblastoma patients with IDH wild-type tumors compared to those with IDH-mutant tumors.…”
Section: Overviewmentioning
confidence: 69%
“… ROC curve analysis showed that serum miR-145–5p could effectively distinguish GBM patients from the control groups. Multivariate analysis confirmed that serum miR-145–5p expression was an independent prognostic indicator for overall survival in GBM patients Díaz Méndez et al ( Diaz Mendez et al, 2023 ) 2023 miR-1-3p Underexpressed Serum Diagnosis, Prognosis A 3-microRNA signature consisting of miR-1-3p, miR-26a-1-3p, and miR-487 b-3p was found to be differentially expressed in the serum of glioma patients compared to healthy controls. This 3-microRNA signature was specifically downregulated in the serum of glioblastoma patients with IDH wild-type tumors compared to those with IDH-mutant tumors.…”
Section: Overviewmentioning
confidence: 69%
“…The signature was more downregulated in IDH -wildtype samples compared to IDH -mutant or in controls with normal IDH . Given that the three miRNAs are tumor suppressors, the authors reported that their levels were informative for OS and PFS [ 59 ].…”
Section: Deregulated Mirnasmentioning
confidence: 99%
“…Recently, we identified a serum miRNA signature (miR-1, miR-26a-1 and miR-487b) deregulated in glioma patients according to the IDH mutation profile and correlated with the prognosis. We also showed that the three-miRNA signature displays oncosuppressive functions in glioma cells with the most marked effect on proteins crucial for migration and invasion [ 24 ] (Fig. 10 A).…”
Section: A Diagnostic Circulating Mirna Signature In Human Gliomas As...mentioning
confidence: 99%